2018
DOI: 10.4314/as.v17i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary inclusion of biochar on growth performance, haematology and serum lipid profile of broiler birds

Abstract: One hundred and twenty (120) day-old broiler birds were used to ascertain the effect of dietary inclusion of biochar on the growth, hematology and serum lipid profiles of birds in a 56-day feeding trial. The birds were randomly assigned to 4 groups of 30 birds each, replicated twice with 15 birds per replicate. The groups were randomly assigned to four diets in a completely randomized design involving four levels (0, 2, 4 and 6%) of biochar kg-1. Treatments did not differ significantly (P > 0.05) in final body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
9
13
1
Order By: Relevance
“…The results of an experiment in which poultry were fed biochar, bentonite or zeolite showed that biochar had the best granulation properties (1-4 mm) and moisture retention (85-90%). Dim et al (2018) reported that broilers fed with 4% and 6% corn stover biochar were similar in final body weight but heavier (p < .05) than those fed 2% biochar kg À1 and those on the control diet (0% biochar kg À1 ).The FCR improved from 3.02 (Control) to 1.89 (6%) (p < .05). Egg-laying poultry fed with wood-based biochar had better egg weights (60.6 g ± 1.14 g) and FCR (2.20 g ± 0.042 g) when compared to the control group (without biochar) .…”
Section: Poultry: Chicken and Ducksmentioning
confidence: 97%
“…The results of an experiment in which poultry were fed biochar, bentonite or zeolite showed that biochar had the best granulation properties (1-4 mm) and moisture retention (85-90%). Dim et al (2018) reported that broilers fed with 4% and 6% corn stover biochar were similar in final body weight but heavier (p < .05) than those fed 2% biochar kg À1 and those on the control diet (0% biochar kg À1 ).The FCR improved from 3.02 (Control) to 1.89 (6%) (p < .05). Egg-laying poultry fed with wood-based biochar had better egg weights (60.6 g ± 1.14 g) and FCR (2.20 g ± 0.042 g) when compared to the control group (without biochar) .…”
Section: Poultry: Chicken and Ducksmentioning
confidence: 97%
“…Majewska and Zaborowski (2003) however reported that AC supplemented birds were 1-6.5% heavier, 5.9% better in their FCR and 1.6% better in their survival rate than the control group. Dim et al (2018) reported that the final body weight, average daily weight gain and FCR were better in birds on 6% AC inclusion than other groups after 56 days trial period similar to the reports of Kutlu et al (1999). Dim et al (2018) also noted that WBC count and PCV were not affected at both the starter and finisher phases, while haemoglobin concentration (Hb) and RBC count were significantly improved and cholesterol and lipoprotein levels were significantly reduced, probably due to the ability of the birds on AC to maximally utilize the vitamin-mineral premix in the diet.…”
Section: Effect On Growth Haematology and Serum Chemical Profilesmentioning
confidence: 99%
“…Despite this status, it has not been able to meet the demand of the ever increasing human population, who depend directly on the meat for animal protein and consequently essential amino acids. In a bid to boost productivity, several dietary manipulations have been carried out on poultry, ranging from inclusion of growth promoters (Barreto et al, 2008;Mokhtari et al, 2010), hormones (Al-Dobaib and Mousa, 2009), organic acids (Ghazalah et al, 2011), enzymes (Chuka, 2014;Hossain et al, 2014), locally sourced additives (Onyimonyi et al, 2012;Olabode et al, 2013;Dim et al, 2018), etc.…”
Section: Introductionmentioning
confidence: 99%